Formation of the TNI Cyber Force: A Strategic and Policy Analysis - Aris Sarjito (Defense and Security Studies)
The increasing cyber threats in Indonesia require strengthening the country's defense strategy. This study focuses on the formation of the Indonesian National Army (TNI) Cyber Force as part of efforts to strengthen the country's cyber security in facing increasingly complex threats. The purpose of this study is to analyze the policy and strategy for the formation of the TNI Cyber Force and evaluate the synergy between institutions, especially with the National Cyber ​​and Crypto Agency (BSSN). This study uses a qualitative method with a secondary data analysis approach, including reports from Fortinet, AwanPintar.id, and national policy documents related to cybersecurity. The research findings show that the TNI Cyber Force has a crucial role in protecting Indonesia's critical infrastructure from the threat of botnets, ransomware, and other cyber-attacks. The synergy between the TNI and BSSN is key to building an effective cyber defense system. Although there has been an increase in cyber readiness, this study found that challenges still exist, including in terms of human resources and the technology used. In conclusion, the formation of the TNI Cyber Force is an important step in dealing with cyber threats, but there needs to be further strengthening in cross-sector coordination and adoption of the latest technology.